Home-based exercise improves quality of life in breast and prostate cancer survivors: A meta-analysis. - Lauren C Bates-Fraser; Sasha Riley; Cameron Stopforth; Kaileigh Moertl; Kyle Edgar; Lee Stoner; Erik D Hanson (PLoS ONE, 2023)
Background Breast (BCa) and prostate (PCa) cancer are two of the most common but survivable cancers. One important component of survivorship that is impacted by treatment long term is diminished quality of life (QoL). Supervised exercise improves QoL and subsequent outcomes but is not accessible for all survivors. Additionally, many factors influence QoL including physical activity (PA), cardiorespiratory fitness (CRF), physical function, and fatigue. However, the COVID-19 pandemic has highlighted the need to increase access to exercise beyond supervised exercise facilities. Home-based exercise may provide a feasible alternative for cancer survivors especially for those living in rural communities. Objectives The primary aim is to investigate the effects of home-based exercise training (Pre-training vs. Post-training) on QoL in BCa/PCa. A secondary aim is to investigate PA, CRF, physical function, and fatigue and potential moderators (age, cancer-type, intervention duration and type). Home-based exercise trials (randomized crossover or quasi-experimental design) with adults (aged 18 years and over) breast or prostate cancer survivors (not currently undergoing chemotherapy or radiation treatment) were eligible for inclusion. Data sources Electronic databases were searched (inception-December 2022) for studies which included adult BCa or PCa survivors (not currently on chemotherapy/radiation), at least measured QoL, and undergoing unsupervised, home-based exercise training. Appraisal and synthesis methods Initially, 819 studies were identified, from which 17 studies (20 effects) involving 692 participants were extracted. Effect sizes were calculated as standardized mean differences (SMD). Data were pooled using a 3-level model with restricted maximum likelihood estimation. Pooled SMD was used to assess the magnitude of effect, where <0.2, 0.2, 0.5, and 0.8 was defined as trivial, small, moderate, and large respectively. Results Home-based exercise resulted in small improvements in QoL (SMD = 0.30, 95% CI 0.01, 0.60, p = 0.042), PA (SMD = 0.49, 95% CI 0.26, 0.75, p<0.001) and CRF (SMD = 0.45, 95% CI -0.01, 0.91, p = 0.056). Physical function (SMD = 0.00, 95% CI -0.21, 0.21, p = 1.000) and fatigue (SMD = -0.61, 95%CI -1.53, 0.32, p = 0.198) did not change. Conclusions Home-based exercise results in small improves QoL in BCa/PCa survivors, independent of cancer type, intervention duration and type, or age. Home-based exercise also improves PA and CRF enhancing survivorship. Therefore, home-based exercise is an efficacious alternative option to improve QoL for BCa and PCa survivors especially for those who live in rural communities or lack access to exercise facilities.